The relationship between individually assessed high-intensity accelerations, high-intensity decelerations, sprints, and technical performances during soccer matches: A full season analysis - Silva, H.; Nakamura, F. Y.; Praça, G.; Ribeiro, J.; Marcelino, R. (Research Quarterly for Exercise and Sport, 2024)
Purpose This longitudinal study analyzed the relationship between players` physical (sprint distances, number of high-intensity accelerations and decelerations assessed with individual and relative thresholds) and technical (retrieved from SofaScore platform) performances during competition.